Use of Statins and Antihypertensive Medications in Relation to Risk of Long-standing Persistent Atrial Fibrillation. (April 2015) - Thacker, Evan L.; Jensen, Paul N.; Psaty, Bruce M.; McKnight, Barbara; Longstreth, W. T.; Dublin, Sascha; Newton, Katherine M.; Smith, Nicholas L.; Siscovick, David S.; Heckbert, Susan R.
Background: After an initial episode of atrial fibrillation (AF), patients may develop long-standing persistent or permanent AF.Objective: We evaluated whether use of statins, angiotensin converting enzyme (ACE) inhibitors, angiotensin receptor blockers (ARBs), or β-blockers is associated with lower risk of long-standing persistent AF after an initial AF episode.Methods: We conducted a population-based inception cohort study of participants enrolled in Group Health, aged 30 to 84 years, with newly diagnosed AF in 2001-2004. We included only participants whose initial AF episode terminated within 6 months of onset. We ascertained the primary outcome of long-standing persistent AF from medical records, electrocardiograms, and administrative data. We determined time-varying medication use from Group Health pharmacy data.Results: Among 1317 participants with incident AF, 304 developed long-standing persistent AF. Our study suggests that current statin use versus never use may be associated with lower risk for long-standing persistent AF. However, the association was not statistically significant when adjusted for age, sex, cardiovascular risk factors, and current use of antiarrhythmic medication (hazard ratio [HR] = 0.77; 95% CI = 0.57, 1.03). In lagged analyses intended to reduce healthy user bias, current statin use 1 year prior versus never use 1 year prior was not associated with risk for long-standing persistent AF (HR = 0.91; 95% CI = 0.67, 1.24). ACE inhibitor, ARB, and β-blocker use were not associated with risk for long-standing persistent AF.Conclusions: Current statin use may confer protection that wanes after discontinuing use. Alternatively, healthy user bias or chance may explain the association. The association of statin use with long-standing persistent AF warrants further investigation.